2020
DOI: 10.1002/chem.201904724
|View full text |Cite
|
Sign up to set email alerts
|

Two Push–Pull Channels Enhance the Dinitrogen Activation by Borylene Compounds

Abstract: Recently, Braunschweig et al. found that borylene (CAAC)DurB, in which CAAC is a cyclic alkyl(amino) carbene and Dur refers to 2,3,5,6‐tetramethylphenyl, can bind and activate N2, and the resulting [(CAAC)DurB]2N2 is of a bent BNNB core. The N2 ligand in transition metal complexes is generally linear, so herein, the bonding nature of both terminal end‐on and end‐on bridging borylene‐N2 complexes is investigated with valence bond (VB) theory. In the terminal end‐on (CAAC)HBN2 the bonding follows the mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 60 publications
(39 reference statements)
0
36
0
Order By: Relevance
“…Activation of N 2 molecules and weakening of its π bonds can mainly be attributed to interactions that donate electron density to its π* antibonding orbitals, and remove electron density from the π bonding orbitals of N 2 [21] . Unlike transition metal complexes, which provide a σ acceptor and a π donor orbital to form N 2 complexes (Figure 5 c), singlet FB can be viewed as an electrophilic σ donor and π acceptor (Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of N 2 molecules and weakening of its π bonds can mainly be attributed to interactions that donate electron density to its π* antibonding orbitals, and remove electron density from the π bonding orbitals of N 2 [21] . Unlike transition metal complexes, which provide a σ acceptor and a π donor orbital to form N 2 complexes (Figure 5 c), singlet FB can be viewed as an electrophilic σ donor and π acceptor (Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of N 2 molecules and weakening of its p bonds can mainly be attributed to interactions that donate electron density to its p*a ntibonding orbitals,a nd remove electron density from the p bonding orbitals of N 2 . [21] Unlike transition metal complexes,w hich provide a s acceptor and a p donor orbital to form N 2 complexes (Figure 5c), singlet FB can be viewed as an electrophilic s donor and p acceptor (Figure 5a). Its side-on attack on N 2 (Figures 5c and S12) enables electron donation from its sigma donor orbital into the p*M Oo fN 2 and removal of p-bonding electrons into the p*M Oo fB F. These bonding interactions are supported by an energy decomposition analysis (EDA).…”
Section: Methodsmentioning
confidence: 99%
“… [148] Zhang et al. have computationally studied the role of cAAC ligands in the activation of dinitrogen by borylenes [149] …”
Section: Areas Of Caac Chemistrymentioning
confidence: 99%
“…[148] Zhang et al have computationally studied the role of cAAC ligands in the activation of dinitrogen by borylenes. [149] Unlike transition metal carbonyls, Radacki et al reported the conversion of a cAAC based boryl radical (75) to cAAC-stabilized borylene carbonyl complex (76) in the presence of KC 8 and CO. The further one-electron reduction of 76 produces a novel dimeric borylketyl radical anion (77) by intramolecular Dipp group transfer to the carbonyl carbon.…”
Section: Caac Chemistry Of Group 13 Elementsmentioning
confidence: 99%
“…Scheme 19. Dinitrogen activation by borylene species (Dur = duryl, Dipp = 2,6-diisopropylphenyl, CAAC = cyclic alkyl amino carbene).DFT calculations by the team of Mo with the use of block localized wavefunctions on a simplified model have shed light on this particular bonding 167. They have shown that it is the result of two opposite and perpendicular push-pull channels and interactions with the orbitals of N2 with p geometry only, as well as the uniqueness of borylenes for acting both as a Lewis acid and Lewis base.…”
mentioning
confidence: 99%